Big Data Analytics and Business Pattern Recognition - Ajit Kumar Singh; Prof (Dr) G. P. Gadkar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2023)
In today’s digital era, organizations are inundated with vast amounts of data, presenting both challenges and opportunities for businesses. Big data analytics has emerged as a powerful tool to extract valuable insights from this abundance of data. However, for organizations to derive maximum benefit from big data analytics, alignment with business objectives is crucial. This paper explores the relationship between big data analytics and business alignment, aiming to elucidate the ways in which organizations can effectively integrate analytics into their strategic decision-making processes. The research begins by providing an overview of big data analytics and its significance in the contemporary business landscape. It then delves into the concept of business alignment, elucidating its importance for organizational success. Drawing on existing literature and empirical studies, the paper examines the various dimensions of alignment between big data analytics initiatives and business goals, including organizational culture, leadership support, technological infrastructure, and human resources capabilities. Furthermore, the paper investigates the challenges and barriers that organizations may encounter in aligning big data analytics with business objectives, such as data quality issues, skill shortages, and cultural resistance to change. Strategies and best practices for overcoming these challenges are also discussed, drawing on real-world examples and case studies. Ultimately, this research contributes to the growing body of knowledge on big data analytics by highlighting the critical role of business alignment in maximizing the value of analytics investments. By fostering alignment between analytics initiatives and strategic business objectives, organizations can enhance their competitiveness, drive innovation, and achieve sustainable growth in an increasingly data-driven world.